Landslide susceptibility assessment of the Chure Khola Catchment area of the Siwalik region, Central Nepal - Gyawali, Prakash; Tamrakar, Naresh Kazi (Journal of Nepal Geological Society, 2018)
Landslide susceptibility analysis is carried out in the Chure Khola Catchment, between Amlekhganj and the Churia Mai Range of the Bara District, covering area of 20 sq. km. The catchment lies in the Siwalik Hills composing the Siwalik Group of rocks of Middle Miocene to Early Pleistocene age. Owing to the week and fragile geology, the Siwalik Hills are prone to the gully erosion, shallow landslide and debris flow, during the heavy rain storms in monsoon seasons. In the present study, landslide susceptibility assessment was carried out using two methods, rapid field-based assessment and statistical index methods. For the susceptibility mapping of the river bank slopes, field- based method was used. The seven parameters such as slope angle, slope material, reduction to groundwater, effect of drainage, effect of past failure, effect of vegetation cover and effect of land use were used to calculate the factor of safety in the field. The slope areas were classified as highly susceptible (FS<0.7), susceptible (0.7<FS<1), marginally stable (1<FS<1.2) and stable (FS>1.2) categories, and finally, a susceptibility map was prepared. For the total 4.179 sq. km area where rapid field-based assessment was carried out, the areas covered by highly susceptible, susceptible, marginally stable and stable zones are respectively, 21.56%, 22.11%, 17.37% and 38.95%. Among the highly susceptible and susceptible zones identified, 71% sites have experienced recent slope failures. Landslide susceptibility mapping of the whole catchment area was prepared using statistical index method, and considering seven causative parameters such as elevation, slope, slope aspect, curvature, river proximity, stream density and lithology, which were determined and prepared from DEM using Arc GIS. Eighty percent landslides were used as the training sample for the spatial analysis, whereas 20% landslides were used for the validation of the study. The landslide susceptibility map exhibits the areas covered by very high, high, moderate, low and very low susceptibility zones are 47.18%, 25.28%, 19.77%, 3.60% and 4.16%, respectively. Validity of the study was determined using Riemann Sums method. Success Rate Curve shows that 78.04 % of the areas lie under the curve. Evaluating susceptibility in small watershed is important to mitigate shallow landslide related problems and in rehabilitating forest areas in the Churiya Hills of Nepal.